Health Asset Profile and Health Literacy Among Elementary School-Aged Children - Sukaesih, Nunung Siti; Sopiah, Popi; Lindayani, Emi; Pramajati, Hikmat; Ningrum, Dedah; Lindasari, Sri Wulan (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2025)
Background: Mental health issues, nutritional status, physical activity, and smoking behavior are among the most serious health problems among school-aged children, and they are closely linked to health-related behaviors. Literacy skills significantly influence these behaviors at this age; however, health literacy often receives insufficient attention from the government for this age group.Purpose: The purpose of this study was to provide a comprehensive overview of health asset profiles and health literacy among elementary school-aged children.Methods: This cross-sectional study involved 431 sixth-grade students from the Sumedang district, recruited through a cluster sampling method. Various research instruments were employed, including the Family Affluence Scale (FAS III), Rosenberg Self-Esteem Scale (RSES), Health Behaviours in School-Aged Children (HBSC), European Health Literacy Scale (HLS-EU), and the Newest Vital Sign (NVS) survey. Data were self-reported by participants, and BMI measurements were also collected. The Chi-square test was employed for statistical analysis. Results: The results revealed notable variations across the assessed health asset profile sub-variables. Functional health literacy was significantly associated with self-esteem (p<0.001), student behavior (p=0.010), wake-up time (p<0.001), and smoking habit (p<0.001). In contrast, no significant associations were found with family affluence (p=0.868), BMI (p=0.809), physical activity (p=0.087), or bedtime (p=0.092). Gender-based comparisons revealed significant differences between boys and girls in self-esteem (p=0.042), BMI (p<0.001), physical activity (p<0.001), bedtime (p=0.004), wake-up time (p=0.005), and smoking behavior (p=0.001). Conclusion: This study provides a comprehensive overview of health literacy in school-aged children, highlighting variations across health-related behaviors and asset profiles. Significant gender disparities were found in self-esteem, nutritional status, physical activity, bedtime, wake-up time, and smoking behavior. These findings highlight the importance of developing gender-sensitive health promotion strategies to enhance health literacy and promote healthy behaviors from early ages.